2022
DOI: 10.3390/epidemiologia3040040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors with Ideal Cardiovascular Health Metrics in Bangladesh: Analysis of the Nationally Representative STEPS 2018 Survey

Abstract: This study aims to find out the prevalence of the American Heart Association’s (AHA)’s cardiovascular health metrics and associated socio-demographic factors. A secondary analysis of the World Health Organization (WHO) STEPwise approach to surveillance survey 2018 (STEPS 2018) data was conducted. Ideal Cardiovascular Health (ICH) was defined as the presence of 5–7 ideal metrics as defined by the AHA. Design-adjusted multivariable logistic regression was used to determine the associated factors of ICH. In total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…These are somewhat comparable to our overall results. The prevalence of ideal blood pressure of 31.5% in our cohort is lower than gures from Peru (51%) Marshall Islands (46.7%) and Malawi (46.9%) [28,32,40], but comparable to prevalence rates from Bangladesh (29.3%), Nepal (26.3%), Uganda (37%), China (32.3%) and 29.9% (Urban male dwelling Ghanaians) [30][31][32][33][42][43]. The relatively low prevalence of ideal BP in our cohort might be an indirect re ection of the high burden of hypertension in Nigeria characterized by high prevalence of low awareness, high burden of undiagnosed and poor control [5,44].…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…These are somewhat comparable to our overall results. The prevalence of ideal blood pressure of 31.5% in our cohort is lower than gures from Peru (51%) Marshall Islands (46.7%) and Malawi (46.9%) [28,32,40], but comparable to prevalence rates from Bangladesh (29.3%), Nepal (26.3%), Uganda (37%), China (32.3%) and 29.9% (Urban male dwelling Ghanaians) [30][31][32][33][42][43]. The relatively low prevalence of ideal BP in our cohort might be an indirect re ection of the high burden of hypertension in Nigeria characterized by high prevalence of low awareness, high burden of undiagnosed and poor control [5,44].…”
Section: Discussioncontrasting
confidence: 46%
“…The relatively low prevalence of ideal BP in our cohort might be an indirect re ection of the high burden of hypertension in Nigeria characterized by high prevalence of low awareness, high burden of undiagnosed and poor control [5,44]. The prevalence of ideal diet is globally low according to published literature and our nding of 6.1% aligns with this global trend [28][29][30][31][32][33][40][41][42]. This global trend might be attributable to the twin problems of availability and affordability of fruits and vegetables remotely due to urbanization where arable farmlands have been converted for physical urban development [34,45].…”
Section: Discussionmentioning
confidence: 58%
“…Previous analysis conducted in Bangladesh, also using the 2018 STEPS survey, showed that 43% of adults had at least 5 of the LS7 metrics at ideal levels, 36 corresponding to twice the level reported in US adults (17%-18%) using the same approach. 32 , 33 Although we did not find quite this magnitude of difference, possibly because diet was not evaluated, we did observe that Bangladesh had a higher total CVH score than the US, using either 6 or 5 metrics, and a higher score on each CVH metric individually, with the exception of smoking, with Bangladesh having the highest proportion of current smokers (24%).…”
Section: Discussionmentioning
confidence: 90%
“…This is consistent with previous NHANES analysis showing 56% overweight/obese in 1998-94, increasing to 68% in 2005-10. 4 Previous analysis conducted in Bangladesh, also using the 2018 STEPS survey, showed 43% of adults had at least 5 of the LS7 metrics at ideal levels, 36 corresponding to twice the level reported in US adults (17-18%) using the same approach. 32,33 While we did not find quite this magnitude of difference, possibly as diet was not evaluated, we did observe Bangladesh scored higher than the US on total CVH score using either six or five metrics, and on each CVH metric individually with the exception of smoking, where Bangladesh had the highest proportion of current smokers (24%).…”
Section: Discussionmentioning
confidence: 99%